2014
DOI: 10.1139/apnm-2013-0061
|View full text |Cite
|
Sign up to set email alerts
|

Fuel selection during short-term submaximal treadmill exercise in the cold is not affected by pre-exercise low-intensity shivering

Abstract: Exercise and shivering rely on different metabolic pathways and consequently, fuel selection. The present study examined the effects of a pre-exercise low-intensity shivering protocol on fuel selection during submaximal exercise in a cold environment. Nine male subjects exercised 4 times for 60 min at 50% (LOW) or 70% (MOD) of their peak oxygen consumption on a motorized treadmill in a climatic chamber set at 0 °C with (SHIV) and without (CON) a pre-exercise cooling protocol, inducing low-intensity shivering. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…Some previous studies suggested that fuel selection, metabolic pathways and physiological responses may differ between exercise and shivering in mammals (Haman et al, 2005;Gagnon et al, 2014). However, the present study suggests similar muscular adjustments between exercise and shivering in birds.…”
Section: Discussioncontrasting
confidence: 67%
“…Some previous studies suggested that fuel selection, metabolic pathways and physiological responses may differ between exercise and shivering in mammals (Haman et al, 2005;Gagnon et al, 2014). However, the present study suggests similar muscular adjustments between exercise and shivering in birds.…”
Section: Discussioncontrasting
confidence: 67%
“…The contribution of core cooling to shivering activity is ∼67–80%, whereas skin and peripheral tissue cooling account for the remaining portion [16] , [17] . Shivering in the cold increases cortisol and norepinephrine concentrations, known to modulate immune responses [3] , at rest [18] , [19] and during exercise in the cold [20] . The examination of various cold thermal challenges altering endocrine responses, including shivering thermogenesis, could consequently help explain some immune differences from previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…The variability in environmental conditions between studies [21] , [22] complicates the comparison of results as temperatures nearing 5–10°C provided little to no thermal stress due to the increased metabolic heat production from exercise [20] . Additionally, some studies have evaluated immune differences between a cool and a hot environment, neglecting the comparison to a thermoneutral setting where immunity should be unchallenged and represent a control group comparison [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…33 Future studies should utilize a familiarization session for TTE because of substantial intraindividual responses to a TTE 37 and cold acclimation period as seen previous studies. 8,9,38 Additionally, it is necessary to consider that a severe cold exposure would be needed to attest the time-dependent changes in thermoregulatory and metabolic responses. Furthermore, the meals consumed prior to each experimental trial were not standardized.…”
Section: Limitationsmentioning
confidence: 99%
“…6 Although several studies investigated the effect of exercise in the cold on substrate utilization, studies demonstrate conflicting results, with the rate of utilization dependent on factors such as core temperature, intensity, and duration of exercise. [8][9][10][11] Furthermore, a previous study reported that fat utilization increases during mild-to-moderate intensity exercise and decreases during high-intensity exercise. 12 Muscle glycogen depletion has been observed to be greater during exercise in the cold below 25% of VO 2 max when compared to a thermoneutral environment, [13][14][15] whereas fat utilization was greater during walking at 50% and running at 70% VO 2 max in the cold (0°C) compared to warm condition (22°C), 8 indicating that fuel utilization may differ depending on environmental condition, exercise intensity, and duration, as well as core temperature.…”
Section: Introductionmentioning
confidence: 98%